Effects of maternity waiting homes on perinatal deaths in an Ethiopian hospital. A case-control study. (13th November 2019) - Dalla Zuanna, T; Fonzo, M; Sperotto, M; Resti, C; Tsegaye, A; Azzimonti, G; Manenti, F; Putoto, G; Bertoncello, C; Zanovello, S
Abstract: Background: A Maternity Waiting Home (MWH) is a residential facility located near a medical facility, where women with high risk pregnancies can await and be transferred to the medical facility shortly before delivery or earlier if a complication arise. MWH are widespread in the developing countries, to reduce the long distances to reach health facilities. The aim of this study was to investigate whether MWH was an effective strategy in reducing perinatal deaths at Wolisso Hospital in Ethiopia, from 2014 to 2017. This hospital is supported by the Italian NGO Doctors With Africa CUAMM, with a strong commitment to reduce maternal and child mortality. Methods: Through a case-control study, we compared perinatal mortality among women admitted via MWH and women admitted directly to the hospital. Cases were mothers who experienced at least a perinatal death before discharge. For each case, two mothers who gave birth to one or more babies alive until discharge were selected as controls. 3 groups of confounding variables were considered: maternal conditions or related to the current pregnancy, variables related to the delivery and neonatal characteristics. A regression model was built adjusting for each group. Statistically significant variables were combined in a final model. Results: 1175 cases and 2350 controls were included. Women admitted through MWH showed a OR 0.49 (95%CI:0.33-0.71; p < 0.000) for perinatal mortality when adjusted for the maternal/current pregnancy conditions, and a OR 0.60 (95%CI:0.40-0.90, p = 0.013) when adjusted for the delivery variables. In the final model the risk of perinatal mortality for women admitted to MWH was 54% less than those admitted directly to the hospital (OR = 0.46, 95%CI:0.30-0.70; p < 0.000). Conclusions: Our results show a more than halved risk of perinatal death cases for women admitted to the hospital through a MWH in rural Ethiopia, and support the policy implemented by the government in building such structures nearby each hospital. Key messages: Maternity Waiting Home is a structure near a health facility, where pregnant women at risk wait for their delivery. MWH is an easy and effective tool to reduce perinatal deaths in rural Ethiopia.